2012
DOI: 10.5194/hess-16-3293-2012
|View full text |Cite
|
Sign up to set email alerts
|

Depression storage and infiltration effects on overland flow depth-velocity-friction at desert conditions: field plot results and model

Abstract: Abstract. Water infiltration and overland flow are relevant in considering water partition among plant life forms, the sustainability of vegetation and the design of sustainable hydrological models and management. In arid and semi-arid regions, these processes present characteristic trends imposed by the prevailing physical conditions of the upper soil as evolved under water-limited climate. A set of plot-scale field experiments at the semi-arid Patagonian Monte (Argentina) were performed in order to estimate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 59 publications
(81 reference statements)
0
15
0
Order By: Relevance
“…It has been found that surface microtopography controls spatial and temporal variations of overland flow depth and velocity [47,27,18,19]. In addition, greater depths of water ponded in microtopographic depressions tend to increase infiltration [18,37] and unsaturated flow [30]. The spatial variability in surface microtopography also affects surface-subsurface exchange and runoff generation for riparian wetlands [20].…”
Section: Introductionmentioning
confidence: 96%
“…It has been found that surface microtopography controls spatial and temporal variations of overland flow depth and velocity [47,27,18,19]. In addition, greater depths of water ponded in microtopographic depressions tend to increase infiltration [18,37] and unsaturated flow [30]. The spatial variability in surface microtopography also affects surface-subsurface exchange and runoff generation for riparian wetlands [20].…”
Section: Introductionmentioning
confidence: 96%
“…In addition, soil microtopography is useful in describing other physical, hydrologic and biological processes. It was shown for example to control infiltration and runoff amounts (Romkens et al, 2001;Thompson et al, 2010) and plays a central role in ecohydrologic processes such as rainwater redistribution, seed displacement and plant competition (Rossi and Ares, 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…Based on these considerations, visual terrestrial imagery is appealing for monitoring saturation areas that provides complementary information to hydrograph measurements and thus helps better understand hydrological processes. Rossi and Ares () utilized digital camera imagery to capture the microtopographic effect on run‐off movement and depression storage without disturbing the experimental field, a common problem that may produce artefacts in the observed flow characteristics. Similarly, Orlandini et al () used camera imagery to evaluate the dominant classes of flow direction methods in terrain‐based flow direction predictions.…”
Section: Introductionmentioning
confidence: 99%